International Counseling Students’ Perception of Ethics - Karaman, Mehmet A.; Schmit, Michael K.; Ulus, Ihsan C.; Oliver, Marvarene (Journal of International Students, 2018)
International counseling students’ (ICS) perceptions regarding ethical counseling practice and education in the United States were examined using an online survey. The research sample consisted of ICSs who were enrolled in counseling programs throughout the United States. Findings indicated that even though ICSs came from different cultures with different ethical values, they were well aware of the different codes of ethics, reported engaging in ethical behaviors, and adapted themselves to the U.S. culture and education system. The results of this study may help counselor educators and counseling programs to promote and understand international students’ ethical behaviors from a diverse and multicultural standpoint.